Supporting mental health in youth sport: introducing a toolkit for coaches, clubs, and organisations - Walton, C. C.; Carberry, S.; Wilson, M.; Purcell, R.; Olive, L.; Vella, S.; Rice, S. (International Sport Coaching Journal, 2022)
The mental health of young people is of increasing concern, and early intervention prevention strategies are required. Youth sports are potentially effective environments within which to situate interventions due to high participation rates, familiarity to young participants, and the typically positive relationships held with adults within such spaces. However, coaches identify that they require more knowledge to better respond to mental health concerns that may be present among players. Here, we describe a research translation process in which an open-access, evidence-informed resource was developed to support coaches and sports clubs to better respond to athletes in need as well as to create environments that may protect against mental ill-health and promote well-being. The resource includes a toolkit—with an associated checklist—for recreational sport clubs to follow, a guide to responding to young people in need, and a short educational video. We suggest that these practical and applied resources, which can be immediately implemented, may assist in the provision of targeted and structured guidance for coaches` first response intervention with vulnerable young people. Furthermore, these resources can support future efforts by being specifically tailored for the unique locations and cultures that vary among youth sport environments.